IMPLEMENTASI PENYIDIKAN TINDAK PIDANA ILLEGAL LOGGING DI WILAYAH KABUPATEN TOJO UNA UNA - Nurhayati Mardin; Tuti Haryanti; VIvi Nur Qalbi; Adiguna Kharismawan (Al-Adl : Jurnal Hukum, 2024)
Deforestation is a phenomenon that needs to be addressed seriously to preserve the environment. One of the causes of deforestation is illegal logging activities in forest areas. The purpose of this research is to examine the impact of illegal logging, analyze the law enforcement process against illegal logging perpetrators and analyse obstacles in the implementation of law enforcement against illegal logging in Tojo Una-Una Regency. The research method uses empirical juridical research by using a conceptual approach and a case approach. This research concludes that the investigation of the crime of illegal logging in the Tojo Una-Una Regency area is carried out by Investigators at the Tojo Una-Una Police Station and Civil Servant Investigators of the Sulawesi Regional Environmental and Forestry Law Enforcement and Security Centre and obstacles in the implementation of law enforcement come from technical obstacles such as the difficulty of the terrain that must be traversed to reach the forest area,  lack of facilities and infrastructure and lack of personnel at Tojo Una-Una Police Station and investigators of the Sulawesi Regional Environmental and Forestry Law Enforcement and Security Centre to carry out law enforcement duties against illegal logging crimes, as well as obstacles originating from the rule of law or legal substance, especially after the enactment of the Job Creation law.